2016
DOI: 10.1186/s13287-016-0359-3
|View full text |Cite
|
Sign up to set email alerts
|

A reduction in CD90 (THY-1) expression results in increased differentiation of mesenchymal stromal cells

Abstract: BackgroundMesenchymal stromal cells (MSCs) are multipotent progenitor cells used in several cell therapies. MSCs are characterized by the expression of CD73, CD90, and CD105 cell markers, and the absence of CD34, CD45, CD11a, CD19, and HLA-DR cell markers. CD90 is a glycoprotein present in the MSC membranes and also in adult cells and cancer stem cells. The role of CD90 in MSCs remains unknown. Here, we sought to analyse the role that CD90 plays in the characteristic properties of in vitro expanded human MSCs.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
132
4
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 166 publications
(154 citation statements)
references
References 87 publications
16
132
4
2
Order By: Relevance
“…S3A). Although Moraes et al showed that depletion of CD90 in BM‐MSCs stimulated their osteogenic ability , this association was not found in iMSCs generated in our study (Fig. B).…”
Section: Discussioncontrasting
confidence: 80%
“…S3A). Although Moraes et al showed that depletion of CD90 in BM‐MSCs stimulated their osteogenic ability , this association was not found in iMSCs generated in our study (Fig. B).…”
Section: Discussioncontrasting
confidence: 80%
“…The ten batches processed displayed hMSC markers, although CD90 showed some variability relative to the other markers, suggesting that it may be a critical marker of product quality. Indeed, CD90 expression was demonstrated to regulate hMSC differentiation ability . However, this did not appear to impact on any of the donor hMSC's ability to undergo tri‐lineage differentiation.…”
Section: Discussionmentioning
confidence: 96%
“…Moreover, CBD treatment led to the down-regulation of the MSCs markers CD44, CD90, CD166. Interestingly, the downregulation of CD90, CD44, and CD166 has been linked to a more differentiated stem cell phenotype and to a less tumorigenic potential (Moraes et al, 2016). Additionally, we detected others surface markers involved the activation of the immune system which expression was downregulated by CBD such as CD109, CD151, CD40, CD46, CD59, CD68, CD81, CD82, CD99.…”
Section: Discussionmentioning
confidence: 99%